(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Plankton biodiversity serves as ecological indicator of aquatic environment due to their response to environmental changes. Study was carried out for of 6 months (May – October) in Dadin Kowa dam, Gombe state Nigeria. Samples collected using plankton net into a bottles preserve in 5% formalin then transported to the laboratory for identification, counting and for further analysis. SPSS (v.11.0.1) was used for data analysis. Phytoplanktons group recorded Chlorophyta highest (1,960) and lowest (860) in May and July. Bacillariophyta maximum (990) and minimum (450) number in June and September, Cyanophyta maximum (450) in July and Minimum (20) in September. Euglenophyta was only recorded in September (30), Cryptophyta observed only in June (20) and September (20), Dinophyta highest in May and September (40) minimum (10) in August. Xantophyta minimum (10) in August and maximum (30) in October. The Zooplanktons include Brightwellii highest (428) in June lowest (121) in October, Monia highest (97) and lowest (30) in June and September, Diaptomuus highest (112) in May and the lowest (30) in September. Philodina highest (550) in June while lowest (195) in September, Daphnia highest (43) and lowest (26) in May and September. Cyclops highest (70) in July while lowest (35) in September and October, Bdelloid highest (402) in May and lowest (116) in October. Camtocerus highest (76) in May and lowest (35) in September and October, Bidentata highest (331) in May and lowest (49) in October. Torrential rains,